AN EXPLORATORY STUDY OF RELATIONSHIP BETWEEN PSYCHOLOGICAL WELL-BEING AND SWEARING - Dehraj, Duaa; Dehraj, Nayab; Mansoor, Nuzhat; Arshi, Shabnam (PEOPLE: International Journal of Social Sciences, 2017)
The aim of the research was to explore the relationship between Psychological well-being and swearing. Psychological wellbeing is a construct that underlies human capacity to engage and function effectively in existing challenges of life whereas swearing as a mode of communication has been prevailing among the young adults. To assess the relationship, it was hypothesized that there would be a significant relationship between Psychological well-being and swearing, explaining a triangulated relation between psychological well-being, emotional expression (catharsis) and swearing. A total sample of 105 participants falling between the age ranges of 18 to 25 years was selected through convenience sampling from different universities in Karachi. The two measures that were used in the study included Normative Swearing Scale (NSC) and Ryff’s Psychological Well Being Scale... For the statistical analysis, data was entered in the Statistical Package for Social Analysts (SPSS) software and results were acquired by using correlation. Pearson correlation was calculated and the results obtained were found to be non significant (r = -.139) .It explained that there is no relationship between psychological well being and swearing. However, results proved that males use more swear words than females. Moreover, purpose in life was seen to be negatively correlated with swearing. The results suggested that Psychological well-being and Swearing has no significant correlation but it reflected the gender difference in swearing.